Democratic Republic of Sao Tome and Principe : Staff Report for the 2005 Article IV Consultation and First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2006)
Sao Tome and Principe pursued economic reforms and tried to reduce poverty amidst macroeconomic imbalances under the Poverty Reduction and Growth Facility (PRGF) program. Executive Directors supported the authorities' decision to sustain the process of fiscal consolidation, and stressed the need for implementing a good budget and public expenditure management system. They commended the monetary and financial stances and the central bank's international reserve position; welcomed the authorities' commitment to improve coverage, timeliness, and periodicity of basic macroeconomic statistics; and emphasized to accelerate structural reforms and achieve full transparency in oil revenue management.